Non-spherical polymersomes driven by directional aromatic interactions - Luo, Mingyan; Luo, Yunjun; Li, Xiaoyu (Science China materials, 2018)
Polymersomes, nanoscopic polymer vesicles self-as- sembled from synthetic block copolymers, are ideal can- didates for drug delivery and synthetic biology, due to their characteristic of high stability, chemical versatility and surface modifiability. Besides the dimensions, re- searchers have demonstrated that the shape of polymer- somes also plays a crucial role in their performance [1]. However, the formation of polymersomes is largely dri- ven by the hydrophobic effect [2], which is non-direc- tional, and thus the resultant polymersomes are mostly spherical. Anisotropic polymersomes or vesicular micelles have been reported by van Hest.